The relationship between large cavum septum pellucidum and antisocial behavior, callous‐unemotional traits and psychopathy in adolescents. (31st August 2012) - White, Stuart F.; Brislin, Sarah; Sinclair, Stephen; Fowler, Katherine A.; Pope, Kayla; Blair, R. James R.
<x xml:space="preserve">Abstract</x> Background: The presence of a large cavum septum pellucidum (CSP) has been previously associated with antisocial behavior/psychopathic traits in an adult community sample. Aims: The current study investigated the relationship between a large CSP and symptom severity in disruptive behavior disorders (DBD; conduct disorder and oppositional defiant disorder). Method: Structural MRI scans of youth with DBDs (N = 32) and healthy comparison youth (N = 27) were examined for the presence of a large CSP and if this was related to symptom severity. Results: Replicating previous results, a large CSP was associated with DBD diagnosis, proactive aggression, and level of psychopathic traits in youth. However, the presence of a large CSP was unrelated to aggression or psychopathic traits within the DBD sample. Conclusions: Early brain mal‐development may increase the risk of a DBD diagnosis, but does not mark a particularly severe form of DBD within patients receiving these diagnoses.